Long Noncoding RNA HLA Complex Group 18 Improves the Cell Proliferation of Myocardial Fibroblasts by Regulating the Hsa-microRNA-133a/Epidermal Growth Factor Receptor Axis. (31st July 2022) - Shi, Huoshun; Sun, Lebo; Zheng, Dawei; Xu, Guodong; Shao, Guofeng
Abstract : Hsa-microRNA (has-miR)-133a inactivates the extracellular signal-regulated kinase 1/2 (ERK1/2) pathway and suppresses the cell proliferation of myocardial fibroblasts by downregulation of the epidermal growth factor receptor (EGFR) expression. Bioinformatics analysis exhibits extended noncoding RNA HLA complex group 18 (lncRNA-HCG18) binds to hsa-miR-133a. The purpose of the current experiment is to explore whether lncRNA-HCG18 adsorbed hsa-miR-133a through sponging, resulting in decreased inhibition of hsa-miR-133a on EGFR and ultimately promoting the proliferation of myocardial fibroblasts. To verify and study the correlation and mechanism between lncRNA-HCG18, hsa-miR-133a, and their target genes. Firstly, after overexpression/silencing of lncRNA-HCG18 in myocardial fibroblasts, the level of hsa-miR-133a expression was evaluated by quantitative reverse transcription-polymerase chain reaction (RT-qPCR), and the EGFR, ERK1/2, and p-ERK1/2 expression levels were assessed by Western blotting to confirm that upregulation of EGFR and p-ERK1/2 protein levels by overexpression of lncRNA-HCG18, siRNA lncRNA-HCG18 (siHCG18) reduced the EGFR and p-ERK1/2 protein levels. Then, the luciferase reporter gene system was used to verify that lncRNA-HCG18 regulated EGFR expression by inhibiting the function of the hsa-miR-133a regulatory target gene. Then, a RAP assay was used to confirm that lncRNA-HCG18 interacted with hsa-miR-133a. Finally, the analysis of CCK-8 results indicated that the cell proliferation of myocardial fibroblasts was significantly reduced by siHCG18 while reversed by overexpression of lncRNA-HCG18. Thus, lncRNA-HCG18 inhibited cell viability of cardiac fibroblasts via the hsa-miR-133a/EGFR axis, which was regarded as a regulator of cell proliferation of cardiac fibroblasts in cardiovascular diseases.